The Effects Of Proteın Malnutrıtıon On The Cranıofacıal Growth And Development In Rats - Mustafa Ülgen; İrfan Karadede; Hakan Kaya; Sedat Baran (Galenos Yayinevi, 2001)
In the present study, one control and two experimental groups were composed of Wistar albino rats. The influence of the protein deficiency on the growth and development of the craniofacial skeleton in rats both during the prenatal+postnatal growth, that is from pregnancy to adulthood, and also during the postnatal growth, that is from parturition to adulthood was examined. In order to avoid growth reduction due to nutritional deficiency, the animals were fed ad libitum. At the end of the experimental period, the adult animals were sacrificed and the anthropometric cranial, maxillary and mandibular measurements were made on the skulls. The significant results can be summarized as follows: 1) All of 31 parameters measured in prenatal hypoprotein group were smaller than those of the control group, 2) Half of parameters measured in postnatal hypoprotein group were smaller than those of control group, 3) When prenatal and postnatal hypoprotein groups compared with each other, 30 of 31 parameters measured in prenatal hypoprotein group were smaller than those of the postnatal group. Our findings showed that protein malnutrition from prenatal period to adulthood caused cranial, maxillary and mandibular growth and development deficiency significantly more than only postnatal protein malnutrition.